Banks’ Profitability in an Islamized Financial System: Comparative Study between Iran and Sudan - Al-Harbi, Ahmad (International Journal of Islamic Banking and Finance Research, 2020)
The main objective of this paper is to explore and compare the drives of banks’ profitability in Iran and Sudan as both countries Islamized their financial systems, and according to the best of my knowledge is the first paper to compare banks’ profitability on the only two Islamized financial systems in the world, Iran and Sudan. This study employs panel data techniques specifically one-way fixed effect model, data obtained from Bank scope database, to address this paper title for the period 1992-2008. The descriptive statistics results show that Iranian banks are more profitable and have higher loan to total asset ratio in comparison to Sudanese banks. Contrary, Sudanese banks are more liquid; more capitalized and have higher reserves. The regression analysis reported that capital adequacy (positive), loan intensity (negative), management efficiency (negative), lagged GDP growth (positive) and real interest rate (positive) had the same significant effect on banks’ profitability in Iran and Sudan. Meanwhile, liquidity albeit had the same positive effect on banks’ profitability in Iran and Sudan the results were significant in case of Iran. On the other hand, size, credit risk and industry concentration had opposite effect on banks in Iran and Sudan. The effect of size was negative for Iranian banks and positive and insignificant for Sudanese banks. Also, credit risk was negative and significant for Iranian banks and positive for Sudanese banks (insignificant). The same applies for industry concentration as the variable impacted Iranian banks negatively (significant) and Sudanese banks positively (significant).